THE IMPORTANCE OF JOB AUTONOMY AS A DRIVER OF ORGANIZATIONAL COMMITMENT THROUGH WORK - LIFE BALANCE FOR EMPLOYEES IN A LIFE INSURANCE COMPANY - Andreas Reza; Rina Anindita (School of Business, Bogor Agricultural University (SB-IPB), 2021)
This study aimed to figure out the effects of job autonomy, work-life balance, organizational commitment, and job satisfaction as mediating variables. This research was conducted with a survey using a digital questionnaire distributed in June -July 2020 to 170 employees who work in the life insurance industry. Data were analyzed using the Structural Equation Model (SEM). This study showed that good job autonomy increased work-life balance. It also increased job satisfaction. Good work-life balance increased job satisfaction and good work-life increased organizational commitment through job satisfaction. Keywords: job autonomy, job satisfaction, life insurance industry, organizational commitment, work-life balance